Cardiovascular Dysfunction in Spinal Cord Injury - Neysa Calista (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Cardiovascular functions ars altered by the impaired autonomic pathways in cervical and high thoracic spinal cord lesion, resulting in cardiovascular and thermoregulation dysfunction. The interruption of the motor and sensory functions in the high level spinal cord lesion also plays a role in lack of physical activity and reduce muscle metabolic mass, resulting in coronary heart disease and metabolic syndrome, thus premature mortality. Exercise program in these cases should be made specifically and individually related to the dysregulation of autonomic system and possibility impending autonomic dysreflexia.